DIGITAL READING ON READING COMPREHENSION: FROM STUDENTS’ PERCEPTIONS INSIGHT - Ikke Lailatun Nisak (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aimed at investigating the advanced students of English education department perceptions at University of Islam Malang toward the use of digital reading on reading comprehension. The populations of the sample were from the eighth semester students of English Education Department at UNISMA. The researchers evaluated the study by conducting the interview session to the respondents which the interview brought up six items of question related to the research problem of the study. The results found there were positive responds from the participants. They are interested using digital reading for assisting reading comprehension activity. Digital reading benefits were found as a flexible, motivational, and practical tool for assisting reading comprehension. Introducing the role of technology for reading comprehension could be recommended as the respondents stated the implementation of the method assist students in reading comprehension process. keywords: Reading, Reading Comprehension, Digital Reading, Students' Perceptions